A 2‑Year Review of the Rotary‑Supported Ponseti Clubfoot Clinic in Lagos, Nigeria - Adewole, Oladipo A.; Shoga, Matthias O.; Williams, Omolara M.; Famude, Olawale S.; Kayode, Michael O.; Idowu, Samuel O. (Nigerian Journal of Orthopaedics and Trauma, 2019)
Background: The Ponseti method is generally acknowledged to be the gold standard for congenital clubfoot treatment, worldwide. Although this treatment is considered to be cheap and effective, some patients in less affluent climes are unable to afford the treatment, which includes wearing of braces until the age of 4 years. Objectives: This study documents the experience of running a clubfoot clinic with the financial support from three rotary clubs for 2 years and aims to review the impact of the sponsorship and recommend a replication of this model in similar settings. Materials and Methods: This is a retrospective study of patients treated in our clubfoot clinic adopted by the rotary clubs from 20th September 2017 to 20th August 2019. Age at presentation, sex, laterality, Pirani score, number of casts to correction, brace compliance and complications were recorded prospectively in the International Clubfoot Registry hosted by The Center for Bioinformatics and Computational Biology at the University of Iowa, USA, and analysed using Microsoft Excel software. Results: A total of 136 patients were treated, 81 (60%) of which had bilateral deformities, totalling 217 feet. There were 71 males and 65 females, with a male‑to‑female ratio of 1:0.9. The age at first visit ranged from 0 to 10 years. The largest number, 74 patients (54.4%), was aged between 0 and 3 months, but only one was aged above 10 years, at presentation. Using the Pirani score, 71% had severe deformities (Pirani score of 4 and above). The tenotomy rate was 29%. The average number of casts to correction was 4.6. Sixty‑eight patients received braces at subsidised rates of 50% of the cost. Only 5% of the feet relapsed after correction. Conclusion: The rotary club intervention in our clubfoot clinic was associated with an increase in the annual number of patients attending the clinic, but the relapse rates remained the same as with previous studies.